2007
DOI: 10.1111/j.1467-8489.2007.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent statements in contingent valuation studies: inclusive response formats and giving respondents time to think

Abstract: A recent concern in the valuation literature is the uncertainty respondents feel when posed with willingness-to-pay questions for environmental amenities in hypothetical market scenarios. Using a multiple-bounded discrete-choice format, the results indicate that respondents become less ambivalent when allowed considerable time to think about the valuation task before a response is elicited. In particular they tend to reduce the reported willingness to pay associated with low certainty of paying, hence resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Group interactions, however, could have been the driver of increased uncertainty in MacMillan et al's (2002) results, rather than the effect of time to think. Our finding is similar, however, to Svedsater (2007), who found that TTT reduced respondents' uncertainty. Comparing real versus hypothetical (stated) purchases of a diabetes management program, Blumenschein et al (2008) find that dropping respondents who said they were less than "absolutely sure" from the analysis reduced nearly all of the gap between real and hypothetical choice (a standard cheap talk script had no significant effect).…”
Section: Discussionsupporting
confidence: 89%
“…Group interactions, however, could have been the driver of increased uncertainty in MacMillan et al's (2002) results, rather than the effect of time to think. Our finding is similar, however, to Svedsater (2007), who found that TTT reduced respondents' uncertainty. Comparing real versus hypothetical (stated) purchases of a diabetes management program, Blumenschein et al (2008) find that dropping respondents who said they were less than "absolutely sure" from the analysis reduced nearly all of the gap between real and hypothetical choice (a standard cheap talk script had no significant effect).…”
Section: Discussionsupporting
confidence: 89%
“…In similar fashion to Ready et al (1995) and Svedsater (2007), PC responses included, 'I definitely would adopt it', 'I probably would adopt it', 'I would slightly lean towards adopting it', 'I would slightly lean towards not adopting it', 'I probably would not adopt it', and 'I definitely would not adopt it'. Similar to Ready et al (2001), one of two follow-up questions to the DC format was to be answered, depending upon the response.…”
Section: The Surveymentioning
confidence: 99%
“…2001;Groothuis and Whitehead 2002;Alberini et al . 2003;Caudill and Groothuis 2005;Svedsater 2007). Though none of these studies has dealt with technology adoption, two are particularly relevant for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Whittington et al 1992;Cook et al 2007Cook et al , 2012Svedsäter 2007). In such surveys, respondents are interviewed face-to-face in their homes, given a certain time to think about the valuation scenario and their responses (typically one night) and contacted again on the second day to state their WTP or discrete choices.…”
Section: Response Time Modelsmentioning
confidence: 99%